Characteristics of clinical signs, laboratory and instrumental examinations in various mechanisms of development of type 2 myocardial infarction - Dmitrii V. Oblavatckii (Concilium Medicum, 2021)
Aim. To identify different pathogenetic variants of myocardial infarction type 2 (MI-2).